Inactivation of NF-κB2 (p52) restrains hepatic glucagon response via preserving PDE4B induction - Wen-Song Zhang (Nature Portfolio, 2019)
Elevated glucagon level in obesity and diabetes promotes hepatic glucose production and hyperglycemia. Here the authors report that NF-κB2 augments the hepatic glucagon responses by inhibiting PDE4B induction, and that metformin lowers blood glucose in part by inhibiting NF-κB2.